Analysis of Economists and Managers’ Training Quality - Adomaitienė, Roma (Ekonomika, 2002)
The aim of this article is according to customers I quality indicators of university education to estimate conditions of learning and quality of teaching in Lithuanian universities in preparation of economists and managers. The survey of business representatives revealed the requirements and criteria that are elevated to economists and managers prepared in Lithuanian universities. It was found that training of economists and managers in Lithuanian universities are not enough oriented to business demand. Students need not only theoretical or practical knowledge of their speciality. University education has to help open up such attitudes and habits that characterize the responsible, creative and firm economist or manager and that are necessary in alternate market situation. The most important for students are these quality indicators of teaching: interesting presentation of teaching material, importance and actuality of know- ledge and information received during lectures, intelligibility of teaching and others. The results of the students’ interrogation showed that quality of university education does not really satisfy students - the main customers of universities. The majority of students are confident that the improvement of education quality is insufficient and they usually see inadequate efforts of university leaders to improve teaching process. The system of education quality improvement and assurance should be designed as continuous process considering that the quality of final product of university activities is the result of achievements of all previous stages of this process. Continuous and consistent commitment from university top management regarding questions of education quality, participation in the improvement process using Total Quality Management principles. methods and tools is the keystone for the intention of success.